Pull Production Implementation: An Action Research Study - Luis Henrique Rigato Vasconcellos (RAC - Revista de Administração Contemporânea, 2022)
Context: there is little empirical evidence of the relationship between the implementation of lean techniques (such as the pull system) and their real effect on supply chain performance. Objective: the purpose of this paper is to describe the process of implementing the pull production logic in the supply chain, reporting the historical evolution of indicators, such as inventory levels and lead times over 23 months of intervention. Methods: an action research project was carried out describing chain intervention steps in 2017-2019, divided into phases as follows: planning, data collection, implementation of the action, analysis and evaluation of the results. Results: the main contribution was to demonstrate that the production shift from push to pull had a positive impact on lead time, inventory, and planning routines indicators. Inventory levels were reduced by more than 30% and lead times were down approximately 40%. In addition, sales forecast assertiveness increased. Conclusion: this paper may provide a reference for organizations that want to make similar changes in their supply chains and significantly change the planning routine of their suppliers and distributors by implementing the pull logic.